Plan S: take Latin America’s long experience on board - Debat, Humberto Julio; Babini, Dominique (Nature Research, 2020)
We share the spirit of Plan S to achieve full open access to scholarly publications (see go.nature.com/2hszsaf), but we disagree with its implementation guidelines. The plan’s design ignores more than 20 years of widespread experience in open-access publishing in many developing nations, as well as Latin America’s widespread ethos of free-to-publish and free-toread research. To rectify this, the Plan S guidelines need to tackle the longstanding issues of conventional scholarly publishing, including the high concentration of articles in commercial publications. Funders should promote open-access practices that are more globally inclusive, while improving the quality of editorial processes and keeping their control within the scientific community.